2015
DOI: 10.1177/0018726714563810
|View full text |Cite
|
Sign up to set email alerts
|

Ship-shape: Materializing leadership in the British Royal Navy

Abstract: In this article I contribute to posthumanist, actor-network influenced theories of leadership, drawing empirically on qualitative data collected at a Royal Navy shore establishment inGreat Britain. I demonstrate how a fluid network of hybridized relationships between people and things affords shifting and multiple possibilities for making leadership matter. As configurations of actants evolve these affordances are altered, and the blackboxing processes hiding the material actants co-generating leadership effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 61 publications
1
60
0
Order By: Relevance
“…Fairhurst and Cooren (2009) for example explore how the leader is constituted through the inter-actions of a plethora of actants, including followers. In Hawkins' (2015) study of the materialization of leadership in the British Royal Navy the actants include ship, water and history. Her study illustrates how non-sentient actors both limit and make possible various leadership practices that may be unique to such configurations as a 'Royal' Navy.…”
Section: Introductionmentioning
confidence: 99%
“…Fairhurst and Cooren (2009) for example explore how the leader is constituted through the inter-actions of a plethora of actants, including followers. In Hawkins' (2015) study of the materialization of leadership in the British Royal Navy the actants include ship, water and history. Her study illustrates how non-sentient actors both limit and make possible various leadership practices that may be unique to such configurations as a 'Royal' Navy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Callon (2009), the so-called non-humans actively participate in the collective action by influencing it, internally redefining it and changing its direction and trajectories. In other words, the action can only be assessed in the specific context where it is inserted because its limits are not defined by attributes, but by the relationship in question (Hawkins, 2015). Thus, the action cannot be explained, in a reductionist manner, as a definite consequence of any previous action (Callon & Law, 1997), because any actor (human or non-human) has the potential to act, and the action is the result of a continuous process of translation, association and negotiation (Latour, 1999).…”
Section: Actor-network Theory and The Perspective Of Translationmentioning
confidence: 99%
“…Based on historical data, Bruce & Nyland (2011) used the translation perspective to explain how Elton Mayo and the Human Relations School were able to translate the prevailing context and in so doing created a forum in which powerful actors came to agree that the Human Relations school was an innovation worth building and defending. Hawkins (2015) detailed in a study on the Royal Navy establishment in Great Britain how hybridized relationships co-enable possibilities for action that bring to Waldorff (2013) studied the way the organizational actors translated meaning into the development of a new healthcare centre on a municipality in Denmark; she concluded that decision making in the public sector might in practice be less strategic and intentional, so the translation of discourse could also be explained by how successfully the related practices can be developed. In this vein, Villar et al (2019), in a case study of a Brazilian social enterprise, explored the practices of opening up the strategy supporting a translation process, thus minimizing the tensions of organizational hybridism.…”
Section: Actor-network Theory and The Perspective Of Translationmentioning
confidence: 99%
“…Hawkins (2015) acknowledged the lack of "thing-ness" in leadership research and studied various material aspects of leadership in the British Royal Navy shore establishment. Ropo et al (2013;2015) and Ropo and Salovaara (2018) have undertaken a stream of research to study how physical spaces shape and construct leadership in workplace settings.…”
Section: Leadership In Human-materials Relationsmentioning
confidence: 99%
“…Furthermore, leadership is considered to occur, not only in relations between people, but also in human-material relations (Hawkins, 2015;Ropo and Salovaara, 2018;Ropo et al, 2013). The increasing materiality in organisations-such as IT-technology, infrastructure, office space, and documents-has been shown to affect organising and leadership (Carlile et al, 2013;Oborn et al, 2013;Orlikowski and Scott, 2008).…”
Section: Introductionmentioning
confidence: 99%